Bacterial cellulose based superabsorbent production: A promising example for high value-added utilization of clay and biology resources. (15th March 2019) - Luo, Mu-Tan; Huang, Chao; Li, Hai-Long; Guo, Hai-Jun; Chen, Xue-Fang; Xiong, Lian; Chen, Xin-De
Graphical abstract: Highlights: Superabsorbent composite was synthesized from special bacterial cellulose (BC). Bentonite inorganic gel (BIG) was produced as substrate for fermentation. BC was obtained by in situ fermentation. Effect of different factors on the performance of superabsorbent was evaluated. The water absorption capacity of composite is suitable for industrial application. Abstract: Superabsorbent was synthesized from bacterial cellulose (BC) generated by in situ fermentation on bentonite inorganic gel (BIG). For BIG preparation, the effect of sodium agent's type and content, temperature and time of sodium-modification, and gelling agent's type and content on the viscosity of BIG were learned to optimize the synthesis process. For polymerization, the effect of different factors including ratio of monomer to substrate (modified BC from in situ fermentation), content of initiator and crosslinker, monomer neutralization degree, reaction temperature and time on the performance of composite (superabsorbent) synthesized were analyzed. Under optimal condition, the composite showed good water absorption, salts absorption, and water retention capacity. The original bentonite, sodium-based bentonite, BIG and composite structure was characterized by X-ray fluorescence (XRF), nuclear magnetic resonance (NMR), Fourier transform infrared spectroscopy (FT-IR), scanning electron microscope (SEM) and thermogravimetric analysis (TGA), and the characterization partly explained the performance of water absorption and thermal stability of the composite. Overall, this study provides one method for superabsorbent synthesis from low-cost and natural resources.